1965
DOI: 10.1037/h0021880
|View full text |Cite
|
Sign up to set email alerts
|

Leader behavior, group productivity, and rating of least preferred co-worker.

Abstract: active defensive process described above, two different sources of data provide some indirect evidence for such a process. This evidence is admittedly very weak, and it is hoped that subsequent studies will allow a more exact specification of the mechanisms involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1968
1968
2001
2001

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 2 publications
2
11
0
Order By: Relevance
“…Research shows that relationship-motivated (high LPC) leaders tend to be directive in conditions of high situational control while task-motivated (low LPC) leaders tend to be directive under conditions of moderate and low situational control (Bons & Fiedler, 1976;Fiedler & Garcia, 1987;Larson & Rowland, 1973;Sample & Wilson, 1965;Shirakashi, 1980). The effects of the interaction between LPC and situational control are at best moderate.…”
Section: Discussion and A Look Aheadmentioning
confidence: 99%
“…Research shows that relationship-motivated (high LPC) leaders tend to be directive in conditions of high situational control while task-motivated (low LPC) leaders tend to be directive under conditions of moderate and low situational control (Bons & Fiedler, 1976;Fiedler & Garcia, 1987;Larson & Rowland, 1973;Sample & Wilson, 1965;Shirakashi, 1980). The effects of the interaction between LPC and situational control are at best moderate.…”
Section: Discussion and A Look Aheadmentioning
confidence: 99%
“…Support for this argument has been provided by empirical findings with regard to the emergence of an inner circle around the leader. Sample and Wilson (1965) found that the task-oriented leader maintained a psychological distance from the group as a whole but was closer to those who made the greatest contribution to task accomplishment. Graen's (1976) Leader-Member Exchange (LMX) model shows how the leader establishes a close relationship with highly effective subordinates.…”
Section: Lmx and The Routinization Of Charismamentioning
confidence: 95%
“…On the other hand, the input factors and interaction process as well as process factors and end results have a logic relationship to each other, and it is of benefit to scrutinize this in more detail. The most important input factors that have been shown to be in connection with the team's interaction process are the attitudes of the team leader (13), personal characteristics of the team members (14), the size of the team (15), composition of the team (16) as well as the team's history or its experience (17). It has, futhermore, been found that the characteristics and nature of the task forms a factor, which strongly changes the communicational contents (18)(19)(20)(21)(22).…”
Section: Input and Process Factors In Team Workmentioning
confidence: 99%